Effectiveness of SVRK Learning Model to Improve English Language Ability of Kahuripan Kediri University Agricultural Students - Suhaimi, Imam; Mardatilla, Indana (Universitas Nusantara PGRI Kediri, 2019)
The purpose of this study is to find out the English language skills of students after using the SVRK learning model in learning English for agricultural students. The researchers wanted to find out whether the SVRK learning model could improve the English language achievement of Kahuripan Kediri University Faculty of Agriculture students. The sample in this study amounted to 19 students based on the Faculty of Agriculture, University of Kahuripan Kediri. The results showed that it was known that t-value was higher than t-critical = (7.935> 1.734). It can be concluded that there is a significant improvement in English language achievement of students after being taught using the SVRK learning model. So, the researchers provide recommendations to be able to use the SVRK model on learning English classes at the faculty of agriculture in particular and students in other study programs in general.